A Genome Wide Association Study on plasma FV levels identified PLXDC2 as a new modifier of the coagulation process - Thibord, Florian; Hardy, Lise; Ibrahim‐Kosta, Manal; Saut, Noémie; Pulcrano‐Nicolas, Anne‐Sophie; Goumidi, Louisa; Civelek, Mete; Eriksson, Per; Deleuze, Jean‐François; Le Goff, Wilfried; Trégouët, David‐Alexandre; Morange, Pierre‐Emmanuel (Journal of thrombosis and haemostasis, 2019)
Background Factor V (FV) is a circulating protein primarily synthesized in the liver, and mainly present in plasma. It is a major component of the coagulation process. Objective To detect novel genetic loci participating to the regulation of FV plasma levels. Methods We conducted the first Genome Wide Association Study on FV plasma levels in a sample of 510 individuals and replicated the main findings in an independent sample of 1156 individuals. Results In addition to genetic variations at the F5 locus, we identified novel associations at the PLXDC2 locus, with the lead PLXDC2 rs927826 polymorphism explaining ~3.7% (P = 7.5 × 10−15 in the combined discovery and replication samples) of the variability of FV plasma levels. In silico transcriptomic analyses in various cell types confirmed that PLXDC2 expression is positively correlated to F5 expression. SiRNA experiments in human hepatocellular carcinoma cell line confirmed the role of PLXDC2 in modulating factor F5 gene expression, and revealed further influences on F2 and F10 expressions. Conclusion Our study identified PLXDC2 as a new molecular player of the coagulation process.